Associations between media use, self-efficacy, and health literacy among Chinese rural and urban elderly: A moderated mediation model - Yu, Yebo; Wu, Yibo; Huang, Zhen; Sun, Xinying (Frontiers in Public Health, 2023)
Objectives: The influence of media use on health literacy among urban and rural elderly has been unknown in China. This study aims to examine the association between media use and health literacy and to explore the mediating role of self-efficacy and the moderating role of urban-rural residency. Methods: Based on the cross-sectional study of the Psychology and Behavior Investigation of Chinese Residents (PBICR) in 2022, a total of 4070 Chinese old people aged 60 years and above were included. We adopted the simplified New General Self-Efficacy Scale (NGSES) and the simplified Health Literacy Scale-Short Form (HLS-SF) to measure self-efficacy and health literacy. Media use was measured using a self-administrated questionnaire. Results: Results showed that Chinese urban elderly had a higher frequency of media use than rural ones in the aspects of social activities, self-presentation, social action, leisure and entertainment, information acquisition, and business transactions through media (P<0.001). Among all participants, self-presentation (B=0.217, 95%CI:0.040, 0.394), leisure and entertainment (B=0.345, 95%CI: 0.189, 0.502), and information acquisition (B=0.918, 95%CI: 0.761, 1.076) were significantly associated with health literacy. Self-efficacy partially mediated the effect of media use on health literacy (B indirect=0.045, 95%CI: 0.032, 0.058), accounting for 18.37% of the total effect. Urban-rural residency (B=0.049, 95%CI: 0.024, 0.075) moderated the relationship between media use and self-efficacy significantly. Conclusion: The urban-rural gap in health literacy requires more attention. The promotion of media use and self-efficacy may play a role in eliminating health disparities. Limitations: As a cross-sectional study, it could not establish cause-effect relationships.